Field experiments on multipurpose trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Several species of multipurpose trees have been undergoing screening in experimental sites m Burundi, Kenya, Rwanda and Uganda. Calliandra calothyrsus and Sesbania sesban produced large biomass at all sites, out performing any of the Leucaena...